USM, PU PROFILE COOPERATE TO BOLSTER HBP STUDENTS’ CAPACITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 22 January 2016 – The cooperation between Universiti Sains Malaysia (USM) and a hightechnology construction company with extensive experience, PU Profile Sdn. Bhd (PU) was aimed at providing great benefits to the students of USM.